STRATEGI KOMUNIKASI PEMASARAN DALAM MENARIK MINAT PEMASANG IKLAN RADIO KISS FM MEDAN PADA MASA PANDEMI COVID 19 - Susanna Hutapea; Besti Rohana Simbolon (JURNAL SOCIAL OPINION: Jurnal Ilmiah Ilmu Komunikasi, 2021)
This study aims at finding out how the marketing communication strategy used by Kiss FM Radio Medan is to increase the number of advertisers during the Covid-19 pandemic and what factors are inhibiting or supporting the advertising marketing strategy implemented by Radio Kiss FM Medan during the pandemic Covid-19 Descriptive method with a qualitative approach is applied in this research. Several informants or resource persons, who know technical and detailed information about the research problem raised by the researcher were interviewed. From this study, it was concluded that Radio Kiss FM had experienced several obstacles in terms of advertising, especially during the current pandemic, such as a decrease in the number of advertisers and a decrease in activity in the form of events. However, with the strategy and making innovations and various offers, Kiss FM Medan remains confident and survives during the current pandemic.